Гадюка в сиропе: [роман] / Дарья Донцова - Донцова Даpья Аpкадьевна (Иронический детектив, 2002)
Экземпляры: аб. (2007) / Инвентарный номер: 51258 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44